2021
DOI: 10.3389/fonc.2021.709321
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nomogram Based on Preoperative Bi-Parametric MRI and Blood Indices for the Differentiation Between Cystic-Solid Pituitary Adenoma and Craniopharyngioma

Abstract: BackgroundGiven the similarities in clinical manifestations of cystic-solid pituitary adenomas (CS-PAs) and craniopharyngiomas (CPs), this study aims to establish and validate a nomogram based on preoperative imaging features and blood indices to differentiate between CS-PAs and CPs.MethodsA departmental database was searched to identify patients who had undergone tumor resection between January 2012 and December 2020, and those diagnosed with CS-PAs or CPs by histopathology were included. Preoperative magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The results showed that T1WI&T1CE performed better than other images. This finding is consistent with many previous reports that affirmed the value of multi-modal imaging as superior to single-modal imaging for prognostication [ 30 ]. However, it is unknown if T1WI is better for discrimination and prediction of various aspects of PitNETs than T2WI [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that T1WI&T1CE performed better than other images. This finding is consistent with many previous reports that affirmed the value of multi-modal imaging as superior to single-modal imaging for prognostication [ 30 ]. However, it is unknown if T1WI is better for discrimination and prediction of various aspects of PitNETs than T2WI [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Wu et al indicated that PTPN2 could be induced by inflammatory response and oxidative stress and its deficiency depressed glioma cell growth (Wu et al 2019 ). Meanwhile, inflammatory markers, derived from the routinely available parameters in the blood and their derivatives, appear to have the relationship of prognostic value in many tumors including glioma, craniopharyngioma, ad pituitary tumor (Chen et al 2018a , b ; Marinari et al 2020 ; Zhao et al 2021 ). For instance, some studies reported that the white blood cell had the close relation to the proliferation, migration, immune escape, and prognosis of tumors, which particularly existed in many malignant tumors (McMillan 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pearson correlation coefficient (PCC) was first calculated and used to reduce the redundancy of the primary feature set, followed by the principal component analysis (PCA) approach which converted potentially correlated features into principal components that are linearly uncorrelated via orthogonal transformation ( 16 ). Features with a PCC <0.8 were retained after the first-round examination of feature redundancy.…”
Section: Methodsmentioning
confidence: 99%